Association between Three Therapeutic Strategies and Clinical Outcomes of 2009 FIGO Stage IB2/IIA2 Cervical Cancer. (22nd August 2022) - Zhang, Yong; Tang, Xiaobi; Ma, Shanshan; Shen, Meizhu; Jiang, Li; Yuan, Wenchao; Wang, Rensheng; Wu, Fang
Abstract : Objective . The aim of this study was to compare clinical outcomes of three therapeutic strategies in patients with stage IB2/IIA2 cervical cancer. Methods . This is a retrospective cohort study. Patients diagnosed with stage IB2/IIA2 cervical cancer between April 2010 and December 2015 at First Affiliated Hospital of Guangxi Medical University were included and classed into three groups. The primary outcomes were overall survival (OS) and progression-free survival (PFS). The secondary outcomes included toxicity, hospitalization costs, clinical value, and length of stay. Results . 206 patients were included: 104 used primary surgical treatment (PST), 53 used neoadjuvant chemotherapy followed by radical surgery (NAC + RS), and 49 used concurrent chemoradiotherapy (CCRT). Fewer patients with NAC + RS had deep cervical stromal invasion than primary surgical treatment (PST) (P = 0.024 ). 70.2% of PST and 77.4% in NAC + RS required postoperative radiotherapy or chemoradiotherapy (P = 0.634 ). Median follow-up was 57 months and the 3-year OS and PFS in PST, NAC + RS, and CCRT group were 87.5%, 84.9%, 85.7% and 85.6%, 79.2%, 85.7% (P = 0.856 and P = 0.424, respectively). Three therapeutic strategies were not associated with OS and PFS. Hospitalization costs were significantly higher in NAC + RS compared to PST (P < 0.001 ) and CCRT (P < 0.001 ). Length of stay in NAC + RS was longer than PST (P < 0.001 ) and CCRT group (P = 0.07 ). Conclusion . The results of this study tend to suggest that the three therapeutic strategies were equivalent treatment options for patients with 2009 FIGO stage IB2/IIA2 cervical cancer. However, prospective larger studies are needed to confirm this. In addition, we did find that concurrent chemoradiotherapy needed shorter treatment time and less cost.